ISOLATION AND IDENTIFICATION OF FLAVONOIDS FROM WATER FRACTION OF SECANG WOOD (Caesalpinia sappan. L) WITH THIN LAYER CHROMATOGRAPHY AND UV-VIS SPECTROPHOTOMETRY METHODS - Lolyta Fournia Sari; Suparmi Suparmi; Asih Triastuti (Jurnal Ilmiah Farmasi, 2005)
ABSTRACTAim of this research was to determine chemical structure of flavonoid from water fraction ofSappan wood. The flavonoid was isolated by Soxhlet xtraction using methanol and infundation.First, the detection of flavonoid was done using Thin Layer Chromatography (TLC) with statioramphase silica gel GF 254 and mobile phase ethyl acetate : acetyc acid 15 % (9:1 v/v) smoked byNH3, and detected under UV 366 nm, showed 5 spots with hRf 7, 50, 61, 68, and 80. PreparatifTLC was done to water fraction, disolveed in methanol and detected with UV-Visspectrophotometry using diagnostic reagents NaOH, NaOAc, NaOAc+H3BO3, AlCl3, ACl3+HCl andcompared with references. In fraction 1, 2, and 5 showed isoflavon with 7-OH, substitution oxygenin position six. In fraction 3 showed isoflavon with 7-OH, substitution oxygen in position six, 6,7diOH in A ring, and o-diOH in 6,7 or 7,8. In fraction 4 showed isoflavon with 7-OH, substitutionoxygen in 6, o-diOH in 6,7 or 7,8 and 5-OH.Key Words: Caesalpinia Sappan. L, Flavonoid, TLC, UV-Vis Spectrophotometry